ANALISIS SEMIOTIKA ROLAND BARTHES DALAM ANSAMBEL MUSIK IRINGAN TARI PAKKARENA KREASI KARYA ANDI NURHANI SAPADA - Hafid, Mukhsin Putra; Hartati, Tengku; Salawati, Bau (JURNAL PAKARENA, 2025)
Observing the Pakarena Dance performance by Andi Nurhani Sapada, it is undeniable that everyone can have different interpretations. Therefore, the author wants to review the intra and extra aspects of the Pakarena performance, as an aesthetic interaction activity that is arranged into a text. This qualitative study takes a descriptive critical analysis approach, adopting a cultural studies approach to understand the socio-cultural experience generated by aesthetic form. This study shows that the relationship between cultural institutions, Pakarena cultural prroducts-their contents and meaning and values (the effects of the relationship between the two), forms a triangular relationship that is symbiotic mutualistic and aesthetic. This study concludes that intergrating the interaction of aesthetic values in Pakarena tradition is very important for the sustainability of habitus of the Makassar ethnic community.